A systemic view on the distribution of diet-derived methanol and hepatic acetone in mice. (6th December 2017) - Kistler, Martin; Muntean, Andreea; Höllriegl, Vera; Matuschek, Georg; Zimmermann, Ralf; Hoeschen, Christoph; de Angelis, Martin Hrabě; Rozman, Jan
Abstract: Volatile organic compounds (VOCs) from breath can successfully be used to diagnose disease-specific pathological alterations in metabolism. However, the exact origin and underlying biochemical pathways that could be mapped to VOC signatures are mainly unknown. There is a knowledge gap regarding the contribution of tissues, organs, the gut microbiome, and exogenous factors to the 'sum signal' from breath samples. Animal models for human disease such as mutant mice provide the possibility to reproduce genetic predisposition to disease, thereby allowing in-depth analysis of metabolic and biochemical functions. We hypothesized that breath VOCs can be traced back to origins and organ-specific metabolic functions by combining breath concentrations with systemic levels detected in different organs and biological media (breath, blood, feces and urine). For this we fed C57Bl/6N mice a grain-based chow or a purified low-fat diet, thereby modifying the emission of methanol in breath whereas acetone levels were unaffected. We then measured headspace concentrations of both VOCs in ex vivo samples of several biological media. Cecum content especially was identified as a likely source of systemic methanol, whereas the liver showed highest acetone concentrations. Our findings are a first step to the systemic mapping of VOC patterns to metabolic functions in mice because differences between VOCs could be traced to different sources in the body. As a future aim, different levels of so-called omics technologies (genomics, proteomics, metabolomics, and breathomics) could be mapped to metabolic pathways in multiple tissues, deepening our understanding of VOC metabolism and possibly leading to early non-invasive biomarkers for human pathologies.